2014
DOI: 10.1016/j.icarus.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for longitudinal variability of ethane ice on the surface of Pluto

Abstract: a b s t r a c tWe present the results of an investigation using near-infrared spectra of Pluto taken on 72 separate nights using SpeX/IRTF. These data were obtained between 2001 and 2013 at various sub-observer longitudes. The aim of this work was to confirm the presence of ethane ice and to determine any longitudinal trends on the surface of Pluto. We computed models of the continuum near the 2.405 lm band using Hapke theory and calculated an equivalent width of the ethane absorption feature for six evenly-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…They also found evidence for absorption by C 2 H 6 ice, especially in eastern Cthulhu, including the region where the Schmitt et al (2017) LEISA compositional maps place the Cthulhu "core". Ethane was proposed as representative of all alkanes heavier than methane, but confidence in that interpretation is boosted by its identification in higher spectral resolution ground-based observations around the same longitude (Holler et al 2014). Interestingly, Cook et al also found tentative evidence for methanol ice (CH 3 OH), also mostly in eastern Cthulhu.…”
Section: Cthulhumentioning
confidence: 99%
“…They also found evidence for absorption by C 2 H 6 ice, especially in eastern Cthulhu, including the region where the Schmitt et al (2017) LEISA compositional maps place the Cthulhu "core". Ethane was proposed as representative of all alkanes heavier than methane, but confidence in that interpretation is boosted by its identification in higher spectral resolution ground-based observations around the same longitude (Holler et al 2014). Interestingly, Cook et al also found tentative evidence for methanol ice (CH 3 OH), also mostly in eastern Cthulhu.…”
Section: Cthulhumentioning
confidence: 99%
“…Methane and ethane have been probed on Titan (Griffith et al 2006), Pluto (Holler et al 2014), Makemake (Brown et al 2015), and Quaoar (Dalle Ore et al 2009). Also, low-temperature interstellar ices have been shown to primarily contain water (H 2 O), ammonia (NH 3 ), carbon dioxide (CO 2 ), carbon monoxide (CO), methanol (CH 3 OH), and even methane (CH 4 ), with the latter at a level of a few percent (Boogert et al 2015).…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…The detection of ethane (C 2 H 6 ) in the atmospheres of the planetsJupiter, Saturn, Uranus, and Neptune (Gillett & Forrest 1974;Ridgway 1974;Hammel et al 2006) as well as inTitan, Pluto, Quaoar, Makemake (Nakamura et al 2000;Niemann et al 2005;Griffith et al 2006;Dalle Ore et al 2009;Holler et al 2014;Brown et al 2015), and comets including C/ 1996 B2 Hyakutake, 153P/Ikeya -Zhang, C/2001A2, and C/ 1999H1 (DiSanti & Mumma 2008, shows that ethane is a common molecule that deserves the attention of the astrochemistry community. According to Mumma et al (1996), ethane detected in comet C/1996 B2 Hyakutake is likely of interstellar origin based upon its relative abundance to water and can be traced back to the energetic processing of methane ice (Boogert et al 2015) in interstellar clouds, as shown in laboratory experiments simulating the irradiation of pure methane ice (Gerakines et al 1996;Kaiser & Roessler 1998;Bennett et al 2006;Jones & Kaiser 2013), and inmixtures of methane with water (Moore & Hudson 1998) by ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the presence of intermediate products between methane and the presumed long-chain hydrocarbons that produce the red visible colors has been scant, however. Ethane, one of the first irradiation products of methane, has been detected robustly on Makemake (Brown et al 2007) and more weakly on Quaoar (Schaller & Brown 2007a) and Pluto (DeMeo et al 2010;Holler et al 2014).…”
Section: Introductionmentioning
confidence: 99%